Can participation in cooperatives promote the adoption of green production techniques by Chinese apple growers: Counterfactual estimation based on propensity score matching - Li, Dongjian; Dang, Hongmin; Yu, Jin (Frontiers in Environmental Science, 2022)
As one of the key links of agricultural green sustainable development, it is an effective path to popularize green production technology and promote farmers' adoption of green production technology by using cooperatives as an organizational vehicle. Based on the survey of 314 apple farmers in Shaanxi and Gansu provinces, the degree of adoption of green production technology was measured by the coefficient of variation method. At the same time, in view of the selection bias of farmers' participation in cooperatives, the propensity score matching method was used to evaluate the influence of farmers' participation in cooperatives on the adoption of green production techniques. The results showed that participation in cooperatives increases the probability of farmers adopting green production techniques from 25.29% to 30.29%, indicating that cooperatives increase the degree to which farmers adopt green production techniques. In addition, increased cognition of green production, which increases the price and net profit of products sold and reduces expectations of green production risks, is the primary channel through which cooperatives lead farmers to adopt green production technologies. Participation in cooperatives, though, increased input costs for apple production. In order to strengthen the active role of cooperatives in the popularization of green production technologies, more support should be given to cooperatives, and emphasis should be placed on strengthening their institutional development so that they can be standardized and developed at a high quality.